Sistem Pendukung Keputusan Pemberian Kredit Kepada Kreditur Dengan Metode SAW Berbasis Web - Jarot Dian Susatyono Jarot (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
BPR ARTA MAKMUR is a company engaged in Banking and Rural Credit which of course already has many customers. In the process of working, BPR Arta Makmur has served Savings and Credit Savings for the people. In recent times the process of applying for Credit Loans for people who do not have a business has increased, and the company has become quite inconvenient in processing loan applications submitted by prospective BPR customers because they have to select one by one based on the requirements set by the company. With so many credit applicants entering the credit department, it makes the credit department a hassle to decide the results of the application. So that the researcher decided to provide a solution for the Credit Decision Support System using the SAW method with existing criteria in BPR, namely; 1. Required documents, Applicant Status (Employee, Entrepreneur, Civil Servant, etc.), Creditor Capability, Home Ownership, Creditor Capital. By creating a Decision Support System this can help and facilitate BPR in making decisions whether the credit applicant is approved or not in a short time.